APPLICATION FIELD SALES COMPANY FACE PHOTOGRAPHY IN GALUH WASTU KENCANA USING MICROSOFT VISUAL BASIC 6.0 - Yagat Yagat; Susi Wagiyati P, SKom, MMSI (Jurnal Sistem Informasi, 2004)
Computer Use in the Company field of photography, is something very important, asa material to store data sales, reservations, articles and reports. Computers are nolonger regarded as an expenditure or waste of funds but as unjung spear from theservice business. Because the computer is a tool supporting the success of a business.Therefore this paper tries to present a draft administrative information system of dataprocessing in PT. Galuh Wastu Kencana order activity continues to be made apayment program with the application programming language Visual Basic 6.0 underadministrative control. With computerized data expected, it can be processedcorrectly, quickly and accurately.